2017
DOI: 10.21037/jtd.2017.07.93
|View full text |Cite
|
Sign up to set email alerts
|

Inter-hospital transports on extracorporeal membrane oxygenation in different health-care systems

Abstract: Quality follow-up varies. Some keep track of adverse events and report whereas most transport entities do not seem to prioritize this. There is no international body for ECMO transports. Such would be the key for definitions, support, networking, and a registry that successively would increase knowledge concerning adverse events, morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…The ELSO Registry showed that minimum number of ECMO therapies to achieve good outcomes is six per year but more than 30 annual adult ECMO applications were associated with significantly lower mortality (25)(26)(27)(28)(29)(30)(31). The main mission of ELSO is to collect registry of ECMO treatments and provide guidelines associated with ECMO treatment, also for ECMO transport (24).…”
Section: Ecmo Reactivationmentioning
confidence: 99%
See 3 more Smart Citations
“…The ELSO Registry showed that minimum number of ECMO therapies to achieve good outcomes is six per year but more than 30 annual adult ECMO applications were associated with significantly lower mortality (25)(26)(27)(28)(29)(30)(31). The main mission of ELSO is to collect registry of ECMO treatments and provide guidelines associated with ECMO treatment, also for ECMO transport (24).…”
Section: Ecmo Reactivationmentioning
confidence: 99%
“…In Europe, there are several such centers (Rastatt, Karolinska, Bochum, Leicester) (25)(26)(27)(28)(29)(30)(31). Due to the lack of system solutions, comprehensive procedures, adequate training and the number of personnel as well as the lack of intensive care places, the potential of perfusion therapy in Poland is not fully utilized.…”
Section: Ecmo Reactivation In Polandmentioning
confidence: 99%
See 2 more Smart Citations
“…To further categorize the adverse events, the authors examined their own data (452 patients). 2 They identified adverse events in 112 (25.5%) transports, with more than half being significant in nature.…”
mentioning
confidence: 99%